2022
DOI: 10.1093/ajcn/nqac236
|View full text |Cite
|
Sign up to set email alerts
|

Associations of erythrocyte omega-3 fatty acids with cognition, brain imaging and biomarkers in the Alzheimer’s disease neuroimaging initiative: cross-sectional and longitudinal retrospective analyses

Abstract: Background The association between omega-3 (ω-3) PUFAs and cognition, brain imaging and biomarkers is still not fully established. Objectives The aim was to analyze the cross-sectional and retrospective longitudinal associations between erythrocyte ω-3 index and cognition, brain imaging, and biomarkers among older adults. Methods A total of 832 Alzheimer's Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
0
6
1
Order By: Relevance
“…To our knowledge, only one other observational study has investigated the relationship between O3I and MoCA scorev. In contrast to our findings, Rouch and colleagues ( Rouch et al, 2022 ) found no associations between O3I and several measures of cognitive function in older (aged 55–97 years) adults in the U.S. and Canada. However, among ApoE ε4 carriers, who would be at increased risk for Alzheimer’s, Rouch et al observed an association between low O3I and both tau accumulation and lower performance on the Weschler Memory Scale (WMS).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only one other observational study has investigated the relationship between O3I and MoCA scorev. In contrast to our findings, Rouch and colleagues ( Rouch et al, 2022 ) found no associations between O3I and several measures of cognitive function in older (aged 55–97 years) adults in the U.S. and Canada. However, among ApoE ε4 carriers, who would be at increased risk for Alzheimer’s, Rouch et al observed an association between low O3I and both tau accumulation and lower performance on the Weschler Memory Scale (WMS).…”
Section: Discussioncontrasting
confidence: 99%
“…Many other researchers have reported significant relationships between O3I and cognitive function. In fact, among the 14 studies reviewed by Rouch et al, ( Rouch et al, 2022 ) only 3 had entirely null findings. ( Coro et al, 2021 , Dretsch et al, 2014 , Erhardt et al, 2021 ) Most of these studies determined that O3I was related to at least some measures of cognitive function.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These results reflect findings from previous studies that have also found significant changes within the PUFA profiles of individuals with cognitive impairment [ 70 , 71 , 72 , 73 ]. It has been shown previously within a number of epidemiological studies that maintaining sufficient levels of PUFAs and, in particular, DHA and precursors of n-3 synthesis, such as α-linolenic acid, may be protective against age-related cognitive decline or dementia, including AD [ 32 , 52 , 70 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ]. The potential protective effects of PUFAs in relation to cognitive impairment may be related to lowering the risk for heart diseases [ 70 , 81 ] or non-haemorrhagic stroke [ 82 ], which has been shown to escalate the risk of developing dementia and its major subtypes [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of The American Journal of Clinical Nutrition , Rouch et al ( 7 ) analyzed the cross-sectional and retrospective longitudinal associations between scores on the erythrocyte ω-3 index and cognition, brain imaging, and biomarkers among older adults in samples from 832 individuals who participated in the Alzheimer's Disease Neuroimaging Initiative (ADNI). A low ω-3 index score was not associated with cognition, hippocampal or increased white matter hyperintensity (WMH) volumes, or brain Positron Emission Tomography (PET) Aβ or tau values after adjustment for demographics.…”
mentioning
confidence: 99%